EYE-TRACKING FOR INVESTIGATION OF DIFFERENT FUNCTIONS OF THE NERVOUS SYSTEM IN HEALTHY STUDENTS AND PATIENTS WITH NEUROLOGICAL CONDITIONS - Akhmadeeva, L.R.; Bahaaaldin Quritem , Muhammad Ahmed; Yagudina , R.A.; Valiev, V.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Eye-tracking can be used as a tool for investigating various functions of the nervous system to gain data about cognitive processes, attention, perception, and control. Eye-tracking is a part of our projects for healthy students and patients with neurological conditions in Ufa, Russia.